Pengaruh Inflasi, Bi-7 Day (Reverse) Repo Rate dan Earning Per Share terhadap Harga Saham PT Bank Syariah Indonesia Periode 2019-2022 - Mira Miranda; Hamzah Robbani (Neolectura, 2023)
This article discusses the effect of Inflation, BI-7 Day Reverse Repo Rate, and Earnings Per Share on stock prices. The dependent variable in this study is the Stock Price. Meanwhile, the independent variables in this study are Inflation, BI-7 Day Reverse Repo Rate, and Earnings Per Share. The sampling technique was carried out using the purposive sampling method, the total sample in this study amounted to 16 quarters of financial statements at PT. Bank Syariah Indonesia, Inflation Report and , BI-7 Day Reverse Repo Rate at Bank Indonesia and Yahoo Finance for the share price for the 2019-2022 period. Data processing is carried out by multiple linear regression analysis with prerequisite tests first. This article finds that partially Inflation and , BI-7 Day Reverse Repo Rate have a negatif direction but have no significant effect on the Stock Price. Meanwhile, Earnings Per Share has a positive and significant direction towards the Stock Price. Meanwhile, inflation, BI-7 Day Reverse Repo Rate, and Earnings Per Share have a simultaneous influence on stock prices.